HbA1c – dependent changes in the anterior segment of the eye in patients with type 2 diabetes - Mazurek, Magdalena; Karczewicz, Danuta; Lubiński, Wojciech; Pietrzak-Nowacka, Maria (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Introduction : The United Kingdom Prospective Diabetes Study and Diabetes Control and Complications Trial showed a linear relationship between the HbA 1c and the incidence of chronic complications of diabetes. They affect many organs, including the structures of the anterior part of the eye. The aim of this study was to evaluate HbA 1c – dependent changes in the anterior segment of the eye in patients with type 2 diabetes. Material and methods : 87 patients (170 eyes) with type 2 diabetes (DM2) seen at the diabetes clinic were enrolled. They were divided into three groups depending on HbA 1c levels. Group A consisted of patients with HbA 1c below 6.5%, group B consisted of patients with HbA 1c levels ranging between 6.5% and 7.5%, whereas group C consisted of patients with HbA 1c above 7.5%. The anterior segment assessment performed in each patient included biomicroscopy, Schirmer test I, gonioscopy, lens opacity rating, the assessment of lid-parallel conjunctival folds, tear break-up time (TBUT), central corneal thickness (CCT), endothelial cell density (ECD), lens thickness evaluation, anterior chamber depth, axial length of the eye and indirect ophthalmoscopy. Serum HbA 1c levels were determined by the Central Laboratory of No. 2 University Hospital in Szczecin. Main outcome measures : Diabetic patients with higher HbA 1c (> 7.5%) levels presented with more advanced features of dry eye syndrome, higher degrees of lens opacity, greater central corneal thickness, decreased endothelial cell density, and blood vessels within the anterior chamber angle. The lens was the thickest in the group with HbA 1c levels ranging between 6.5% and 7.5%. Conclusions : The current results support the elevated risk of ocular complications affecting the anterior segment of the eye in patients with type 2 diabetes mellitus. The majority of these complications are associated with higher HbA 1c levels, which should be taken into account in daily practice.